Uji Aktivitas Antiinflamasi Dekokta Daun Jambu Biji (Psidium guajava) Pada Mencit Jantan (Mus musculus) Galur Swiss Dengan Induksi Ovalbumin - iis siti hapsah (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2018)
Inflammation is a local protective response caused by injury or tissue damage, which serves to destroy, reduce, or confine (sequester) both the injured agent and the injured tissue. Treatment of inflammation using two classes of drugs namely corticosteroids and NSAIDs. Long-term use of NSAIDs and corticosteroids may have gastrointestinal side effects and other toxicity effects. Guava leaves have anti-inflammatory compounds namely flavonoids and ursolic acid. The purpose of this study was to determine the antiinflammatory activity of guava dekokta (Psidium guajava) in inflammatory induced mice with ovalbumin. The study was conducted using 24 mice divided into 6 groups consisting of the positive control group, the negative control group, the control group given diclofenac potassium drug, the test group 1, the test group 2, and the test group 3 which was given a guava leaf decoction with Different doses. Inflammatory induction was performed with an intraplantar 5% intraplantar eggin (ovalbumin) solution. The best dose, however, was test group 1 with a dose of 32 mg / 20gBB with an inhibitory capacity of 65.67% which almost resembled that of the comparison group. Keywords: Antiinflamasi, decocta, guava leaf (Psidium guajava)